Assessment of Nutritional Status of Children Attending Paediatrics OPD of a Tertiary Care Hospital in Eastern Nepal - Thakur, Jitendra; Bhatta, Nisha Keshary; Poudel, Prakash; Shah, Gouri Shankar; Singh, Rupa Rajbandari (Journal of Nepal Paediatric Society, 2018)
Introduction: Malnutrition is one of the major health problem worldwide, especially in developing world and so is in Nepal, the causes being numerous. The objectives of this study were to assess the nutritional status of children attending paediatric OPD of BPKIHS and to find relation of the nutritional status with different factors. Material and Methods: This descriptive cross sectional study was done by face to face interviews using semi-structured questionnaire and anthropometric variables were recorded. Data of total 192 children was analysed by descriptive statistics. p-value <0.05 was considered significant. Results: According to IAP classification 50.52% were malnourished [grade I 65.97%, grade II 26.8%, grade III 7.21%]. According to WHO classification 47.39% stuntedmoderate 89%, severe 11% and 9.89% wasted [moderate 94.73%, severe 5.26%]. Female sex, low education level in mother, low economic status, unavailability of exclusive breast feeding, low birth spacing and hospitalization were significantly associated with malnutrition. Conclusion: Malnutrition is common in children visiting paediatric OPD of BPKIHS. Female sex, maternal illiteracy, poverty, early weaning, birth spacing and hospitalization in past were major risk factors for malnutrition.